Cold recall: Roald Amundsen's reflections from the South Pole - Amundsen, Roald; Kløver, Geir O (Fram Museum, 2011)
Keywords: Antarktis; ekspedisjoner; historie

Polar settlements : location, techniques and conservation - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2011)
Keywords: Antarktis; hvalfangststasjoner; kulturminnevern; polarforskning; polarområdene; turisme

Sydpolsekspedisjonen 1910-1912 - Bjaaland, Olav (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

The ANTOSTRAT Legacy: Science Collaboration and International Transparency in Potential Marine Mineral Resource Exploitation of Antarctica - Cooper, Alan; Barker, Peter; Barrett, Peter; Behrendt, John; Brancolini, Giuliano; Childs, Jonathan; Escutia, Carlota; Jokat, Wilfried; Kristoffersen, Yngve; Leitchenkov, German; Stagg, Howard; Tanahashi, Manabu; et al. (Science Diplomacy: Antarctica, Science, and the Governance of International Spaces, 2011)
Keywords: Antarktis; geopolitikk; internasjonal samarbeid; marin geologi; mineraler; ressurser; stratigrafi; tektonikk

Belgica. South Pole. The Heroic Dogs. Darkness and Light. Amundsen and Byrd - Cox, Lynne (South with the sun : Roald Amundsen, his polar explorations, and the quest for discovery, 2011)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjonen; Sydpolen; oppdagelsesreiser; polarekspedisjoner; sledehunder

Sydpolsekspedisjonen 1910-1912 - Gjertsen, Hjalmar Fredrik (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Hassel, Sverre (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Ecosystem study and krill survey aboard G.O. Sars in Southern Ocean - Iversen, Svein A; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Bouvetøya; Det Internasjonale polaråret 2007; krill; marine økosystemer; plankton; polarforskning

Sydpolsekspedisjonen 1910-1912 - Johansen, Hjalmar (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Das Eis und der Tod : Scott, Amundsen und das Drama am Südpol - Jostmann, Christian (Beck, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Der Wettlauf zum Südpol : das grösste Abenteuer der Geschichte - Knopp, Guido; Sporn, Mario; Schnier, Marten (Bertelsmann, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Seals used as "research assistants" in the polar oceans - Kovacs, Kit M; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Bildeberetninger. Mediebegivenheter. Polprospekter - Lund, Harald Østgaard; Berg, Siv Frøydis (Norske polarheltbilder : 1888-1928, 2011)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; fotografi; fotohistorie; kulturhistorie; polarekspedisjoner; polarområdene; polfarere

Race to the end : Scott, Amundsen and the South Pole - MacPhee, Ross D E (The Natural History Museum, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

På hvalfangst, 1955-56 - Mortensen, Mauritz Sundt (Atlantic Press, 2011)
Keywords: Sørishavet; hvalfangst

Sydpolsekspedisjonen 1910-1914 - Nilsen, Thorvald (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; oseanografi; polarområdene

The present location of the tent that Roald Amundsen left behind at the South Pole in December 1911 - Orheim, Olav (Polar Record, 2011)
Determining the present precise location of Amundsen's tent is a function of 1) the precision of Amundsen's navigation in 1911, 2) the flow of ice since then, and 3) the amount of burial by intervening snow fall. These factors are discussed and it is concluded that the best location that can be given for the tent in December 2011 is 89° 58′ 51″ S, 46° 14′ E, and lying 17 m below the present snow surface. The uncertainty in the position is 0.3 km, and is mainly related to uncertainties in the original positioning. It can be concluded with high certainty that the tent lies between 1.8 and 2.5 km from the South Pole.
Keywords: Antarktis; ekspedisjoner; glasiologi; historie

Le tombeau des glaces : duel mortel pour le pôle - Pierre, Marc (Dorval, 2011)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1912 - Prestrud, Kristian (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Sydpolsekspedisjonen 1910-1914 - Schröer, Adolf Hermann; Hansen, Ludvig; Rønne, Martin; Hanssen, Helmer; Kutschin, Aleksandr; Wisting, Oscar; Stubberud, Jørgen; Doxrud, Christian; Stubberud, Jørgen; Hansen, Ludvig; Rønne, Martin (Frammuseet, 2011)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Antarktis : 71 dager, 1800 kilometer og én million tanker - Skog, Cecilie; Sandberg, Sigri (Gyldendal, 2011)
Keywords: Antarktis; Sydpolen; ekspedisjoner; polarekspedisjoner; reiser; reiseskildringer

Overvåking av havklima i Antarktis - Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor (Klima : norsk magasin for klimaforskning, 2011)
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer

Amundsens omstridte forløper ; Innsjøen under isen - Thuesen, Nils Petter (Vi menn vitenskap & historie, 2011)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Vostoksjøen; ekspedisjoner; glasiologi; subglasial innsjø

Clues to historical climate variation and future changes in sea level buried in the Antarctic ice (TASTE-IDEA) - Winther, Jan-Gunnar; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Dronning Maud Land; glasiologi; havnivåstigning; klimaendringer; polarforskning